APPLICATION OF TRAINING METHODS AND PRACTICE (DRILL AND PRACTICE) - Nofri Lestari; Johanes Sapri (UNIB Press, 2018)
This study aimed to describe the application methods of drill and practice in improving discipline and skill in using hand tools in studying automotive basic work subject class X motorcycle engineering of SMK Negeri 1 Empat Lawang. The type of research and continued with experimental research. The research subjects were class X motorcycle engineering 1 SMK Negeri 1 Empat Lawang, there were 33 students. Data analysis techniques which is used were data average of learning outcome The results of the study showed that and data analysis of t-test. The application of learning methods of drill and practice could improve the skill of hand tools in automotive basic work lesson